PROFIL GURU DI ERA SOCIETY 5.0 - Ni Putu Restu Trinadi Asih; Maria Fitriani Asni; I Wayan Widana (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The era of society 5.0 can be interpreted as a concept of a human-centered and technology-based society. The era of society 5.0 is a continuation of the industrial revolution 4.0’s era which further emphasizes the human side in solving social problems including education by integrating virtual and reality. This study aims to analyze the profile of teachers in the era of society 5.0 by using data sources or references in the form of books, journals, and others. Teachers as an activator in education in this era must have adequate competence. They must be proficient in providing subject matter and able to move students to think critically and creatively. In addition to curriculum preparation and adequate facilities for society 5.0 era education, teachers are expected to be able to ensure the curriculum runs optimally, therefore, teachers must have several main and supporting competencies such as educational competence, competence in strategic future and counselor competence. Teachers also need to have a technology-friendly attitude, collaborative, creative and risk-taking, have a good sense of humor, and teach thoroughly.